Mathematical modeling of the detonation wave structure in the silane-air mixture. Issue 6 (3rd June 2018) - Fedorov, A.V.; Tropin, D.A.; Fomin, P.A.
ABSTRACT: The paper deals with the problem of the structure of detonation waves in the silane-air mixture within the framework of mathematical model of a nonequilibrium gas dynamics. Detailed kinetic scheme of silane oxidation as well as the newly developed reduced kinetic model of detonation combustion of silane are used. On its basis, the detonation wave (DW) structure in stoichiometric silane-air mixture and dependences of Chapman–Jouguet parameters of mixture on stoichiometric ratio between the fuel (silane) and an oxidizer (air) were obtained. It was revealed that in the reaction zone, in the structure of DW, the heat release in the model with detailed kinetics is non-monotonic.